Efficacy of transdermal rotigotine in chronic cluster headache: A case series. (21st November 2018) - Di Lorenzo, Cherubino; Pellesi, Lanfranco; Coppola, Gianluca; Parisi, Vincenzo; Evangelista, Maurizio; Guerzoni, Simona; Rossi, Paolo; Serrao, Mariano; Pini, Luigi Alberto; Pierelli, Francesco
Cluster headache (CH) is one of the most severe forms of headache, but the number of effective treatments is still limited. Recently, we reported the case of a drug-resistant CH patient responsive to the rotigotine transdermal patch, which is used in the treatment of Parkinson's disease. This report formed the basis for a case series where other drug-resistant CH patients were treated with rotigotine. Here are the results of this study. Twenty-two CH patients underwent the treatment. Eight were episodic cluster headache (ECH) patients and 14 were chronic cluster headache (CCH) patients. Of the eight ECH patients, four reported that their CH had been stopped by the treatment. Of the 14 CCH patients, 11 were considered responders to the treatment (5 experienced a full resolution of headache, and 6 had a headache reduction of at least 50% in terms of mean monthly number of attacks). Our case series confirms the previous observation that rotigotine could be helpful in the treatment of CH. It may even influence the monoaminergic system that has a key role in the pathogenesis of CH.